Sex differences in white matter integrity in youths with attention-deficit/hyperactivity disorder: a pilot study - King, Jace B.; Yurgelun-Todd, Deborah; Stoeckel, Amanda; DiMuzio, Jennifer M.; Lopez-Larson, Melissa P. (Frontiers in Neuroscience, 2015)
Widespread disparities in white matter (WM) microstructure and organization have been found in adolescents with attention-deficit/hyperactivity disorder (ADHD); however, little is known about the role sex plays in these differences. The present diffusion tensor imaging (DTI) study performed whole-brain, tract-based, voxel-wise and region of interest (ROI) analyses to investigate WM microstructure differences between ADHD and healthy control (HC) adolescents to examine the impact of sex on measures of fractional anisotropy (FA). Eighteen adolescents with ADHD and 24 HC were included in this study. All participants received a 64-direction DTI scan on a 3 Tesla Siemens scanner. FSL’s TBSS was used to preform whole-brain, tract-based, voxel-wise analyses. Tracts demonstrating significant sex-by-diagnosis interactions were further evaluated using univariate analyses performed on mean FA data that were extracted from ROIs using the Johns Hopkins University WM tractography atlas. TBSS analyses between diagnostic groups revealed significantly increased FA in HC relative to ADHD in the bilateral superior longitudinal fasciculus (SLF), forceps major, left cingulum, and bilateral callosal regions. In addition, both TBSS and separate ROI analyses revealed significant sex-by-diagnosis interactions for the corticospinal tract (CST), inferior longitudinal fasciculus (ILF) and SLF. In the HC group, FA was increased in males relative to females for all analyses. In WM regions demonstrating a significant sex-by-diagnosis, FA was increased in females relative to males in the ADHD group. Our findings suggest that WM microstructure in several major WM tracts differs between males and females with ADHD. These differences in WM microstructure may account for some of the differences in ADHD subtypes and comorbidities seen between the sexes. Additional studies in ADHD, examining sex differences in phenotypic expression, treatment response and brain network trajectories are warranted.